NEUROIMAGING MARKERS AND CLINICAL SEVERITY CORRELATIONS IN VASCULAR ENCEPHALOPATHY: A RETROSPECTIVE COHORT STUDY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Vascular encephalopathy (VE) is a critical cause of cognitive impairment but the correlation between neuroimaging abnormalities and clinical severity is unknown. A retrospective study was conducted on 81 patients with MRI-proved VE to investigate correlations of imaging measures with clinical rating scales. These individuals underwent standard 3T MRI with quantitation of atrophy patterns on the Global Cortical Atrophy scale and white matter lesions on the Fazekas scale. Clinical severity was quantified with the Stephen-Porges autonomic dysfunction scale and PSM25 neurologic deficit scale. The study revealed correlation of severity of atrophy in the frontal lobe with respect to PSM25 scores (β=0.76, p